Performance Effects of Positive and Negative Affective States in a Collaborative Information Seeking Task - Gonzalez-Ibanez, R (Springer Verlag, 2014)
Collaborative information seeking (CIS) is a common process carried out by groups in a wide variety of situations and contexts. From family activities to business tasks, people typically engage in collaborative search practices while working toward a common goal. In collaborative settings, various aspects of human behavior influence the way people interact with each other and make decisions. One of these aspects corresponds to emotions and related affective processes such as mood and feelings. Studies in social psychology have suggested that group dynamics and their performance may be affected by the interaction of affective processes, in particular positive and negative ones. Although such findings have been derived in different group situations, to the best of our knowledge none of them refer to the particular case of CIS. Based on previous studies, we investigate to what extent positive and negative affective states relate to group performance in CIS. To carry out this study, we designed an experiment with 45 dyads distributed in three configurations based on initial affective states: (1) positive-positive, (2) positive-negative, and (3) negative-negative. To achieve these initial conditions, members of each dyad were individually exposed to affective stimuli. Following, each dyad worked on a precision-oriented search task. Our results suggest that the three interactions of affective states have different implications on the performance of dyads. In particular, the negative-negative configuration performed significantly better than the other two configurations. Conversely, performance of the positive-negative condition was found to be significantly lower than the other two conditions. Findings from this work have practical implications for applications such as team design in tasks involving CIS. © 2014 Springer International Publishing.